The Effect of industrial digitalization on total halal meat production in Java - Riduwan Riduwan; Akhmad Kusuma Wardhana (Universitas Airlangga, 2022)
The demand for halal meat in Indonesia is very large. Java Island is an area with a large production of halal meat in Indonesia. This study aims to analyze the effect of the number of digital equipment, Human Development Index levels, and digital payment modes on the productivity level of halal meat in the three largest provinces on the island of Java. This study uses panel data on the number of digital device usage, Human Development Index, number of digital payments, and total production of halal meat in East Java, West Java, and Central Java in 2015-2022. Data were analyzed using Eviews 10 software. The results show that digital devices used in the halal meat industry do not necessarily affect halal meat production in the provinces of East Java, Central Java, and West Java. However, HDI and the number of digital payments have a positive effect on halal meat production in the provinces of East Java, Central Java